Relationship between clinical record completeness and occurrence of adverse events within hospitals. (20th October 2021) - Mellace, F; Scarpis, E; Brunelli, L; Tullio, A; Cautero, P; Londero, C; Farneti, F; Valent, F; Cocconi, R
Abstract: Introduction: Clinical record (CR) is an appropriate source for adverse events (AEs) detection and Italian law requires its compilation. Its completeness is used as an indicator of the quality of care provided and offers guidance on system changes to improve professional practice. This study aimed at assessing the completeness of CRs, describing AEs' rate and triggers, and investigating the relationship between CR completeness and the occurrence of AEs. Methods: A retrospective review of CRs was conducted, randomly selecting patients discharged from Internal Medicine (IM), General Surgery (GS) and Obstetrics (O) between June and September 2020 at the Academic Hospital of Udine (Italy). The completeness of CRs was assessed using a 65-items checklist developed by the hospital Quality Unit. Triggers and rate of AEs were detected by using Global Trigger Tool. Relationship between AEs and completeness of CR was analyzed using nonparametric tests. Results: Among 93 reviewed CRs, 91.4% were from the GS, 5.4% from IM and 3.2% from O. Patient mean age was 64.6±18, women were 51.6%. The average completeness of CRs was 50.4% [30.4%-83.5%]. Identified triggers and AEs were 125 and 29 respectively, with at least one AE every 23.7% admissions, 31.2 AEs per 100 admissions and 40 AEs per 1000 patient-days. The most frequent AEs were surgical damage (51.7%; 15) and hospital-acquired infection (24.1%; 7). Hospitalization length for patients with at least one AE was 12.6 days, whereas it was 6.3 days without AEs. A significant positive correlation (R = 0.36; p < 0.001) was found between length of hospitalization and number of AEs. The increase in CR completeness is associated with the decrease of the total number of AEs (R=-0.18; p = 0.083). Conclusions: These findings suggest a direct association between the number of AEs and the length of hospital stay. The correlation between CR completeness and AEs suggest that patient safety could benefit from the improvement of clinical record compilation. Key messages: More studies are needed to understand if the occurrence of AEs to patients may cause a prolonged length of hospitalization. A better compilation of CRs should allow to reach a more effective communication between healthcare workers, creating a work environment less prone to errors and AEs.